Comparison of Distal Transradial in the Anatomical Snuffbox versus Conventional Transradial Access for Coronary Angiography and Intervention-An Experience in 100 cases - Amin, Md Rasul; Singha, Chayan Kumar; Banerjee, Sajal Krisna; Hoque, Harisul; Mahabub, SM Ear E; Hoque, Mostashirul; Biswas, Eshita (University Heart Journal, 2018)
Background: Distal transradial access in the anatomical snuffbox has advantages over standard proximal access in terms of patient and operator comfort levels and risk of ischemia. Radial artery preservation could be a relevant issue in patients requiring multiple radial artery procedures and coronary bypass with the use of a radial graft or construction of Arterio-Venous fistula in patient of chronic kidney disease. One relevant drawback is the challenging puncture of a small and weak artery, with a steeper learning curve. Objectives:This study sought to compare the feasibility, safety and complications of coronary angiogram and intervention betweenthe distal transradial in the anatomical snuffbox and conventional transradial access. Methods: In this cross sectional studya total of 100 patients were assigned to perform coronary angiogram or intervention through conventional transradial accessand distal transradial in the anatomical snuffboxfrom November 2017 to April 2018 in theDepartment of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU). We divided the total patient in two groups, with 50 patientsin each group. All of them had normal pulse in theirradial and dorsal radial artery.One group was subjected toconventional right transradial accessand another to rightdistal transradial in the anatomical snuffbox.Demographic features &complications were recorded. Results: The overall procedural success was 98% which was greater than expected in our early clinical experience for distal transradial access with 48 successful accesses out of 50 patients and for conventional radial approach it was also 98%.There was failure to access of distal radial artery in two casesthat may be due to hypoplastic/vasospastic distal radial artery and for conventional radial artery radial artery spasm was the cause. Patients of conventional radial access had more spasm, hematoma, numbness and hospital stay (p< 0.001) than distal radial access. Considering all, it may be said thatdistal transradialaccess was very much effective and safe as there was less spasm, more comfortable to the patient, no hand ischemia, hematoma, numbness, and early hospital discharge. Conclusion: Distal transradial access in the anatomical snuffbox for coronary angiogram and intervention is abetter alternative, safe and feasible option to conventional transradial access for both patients and operators. University Heart Journal Vol. 13, No. 2, July 2017; 40-45